2020
DOI: 10.1002/ange.202007886
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination Enhances NIR‐II Fluorescence of Polymer Dots for Quantitative Brain Tumor Imaging

Abstract: Here, we describe a fluorination strategy for semiconducting polymers for the development of highly bright second near‐infrared region (NIR‐II) probes. Tetrafluorination yielded a fluorescence QY of 3.2 % for the polymer dots (Pdots), over a 3‐fold enhancement compared to non‐fluorinated counterparts. The fluorescence enhancement was attributable to a nanoscale fluorous effect in the Pdots that maintained the molecular planarity and minimized the structure distortion between the excited state and ground state,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Upconversion nanoparticles are developed based on their deep tissue penetration and weak background interference, yet complex mechanisms associated with a nonlinear photon upconversion impede quantification by means of fluorescence intensity. Semiconducting polymer dots (Pdots) have received considerable attention in biology and medicine. Various Pdots have been demonstrated in applications such as optical imaging, photoacoustic imaging, biosensing, phototherapy, and drug delivery. Pdots exhibit stable fluorescence intensity in a physiological environment comprising biologically relevant ions and ROS . The Pdots also remain highly dispersed without a sign of aggregation in a biological medium.…”
mentioning
confidence: 99%
“…Upconversion nanoparticles are developed based on their deep tissue penetration and weak background interference, yet complex mechanisms associated with a nonlinear photon upconversion impede quantification by means of fluorescence intensity. Semiconducting polymer dots (Pdots) have received considerable attention in biology and medicine. Various Pdots have been demonstrated in applications such as optical imaging, photoacoustic imaging, biosensing, phototherapy, and drug delivery. Pdots exhibit stable fluorescence intensity in a physiological environment comprising biologically relevant ions and ROS . The Pdots also remain highly dispersed without a sign of aggregation in a biological medium.…”
mentioning
confidence: 99%
“…As a result, the development of a multifunctional nanoplatform capable of crossing the BBB and targeting gliomas is critical for the high-sensitivity detection and ablation of cancer cells. Although Pdots-based FL imaging for glioma detection was carried out [110,111,115], as exogenous substances, they are easily recognized by the immune system and quickly cleaned by the liver and kidney [110]. Additionally, pure Pdots have difficulties in crossing BBB and specifically targeting brain tumor tissue.…”
Section: Pdots For Glioma Imagingmentioning
confidence: 99%
“…On the other hand, halogenation is a feasible strategy to influence the photophysical properties of organic dyes, such as photostability, molecular packing, emission efficiency, and so on [38–48] . Some studies have also been conducted and reported to investigate the effects of halogen substitutions on AIEgens [49–55] .…”
Section: Introductionmentioning
confidence: 99%